2016
DOI: 10.1002/asi.23730
|View full text |Cite
|
Sign up to set email alerts
|

Data reusers' trust development

Abstract: Data reuse refers to the secondary use of data—not for its original purpose but for studying new problems. Although reusing data might not yet be the norm in every discipline, the benefits of reusing shared data have been asserted by a number of researchers, and data reuse has been a major concern in many disciplines. Assessing data for trustworthiness becomes important in data reuse with the growth in data creation because of the lack of standards for ensuring data quality and potential harm from using poor‐q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 50 publications
2
104
0
Order By: Relevance
“…Several recent studies have investigated data reuse practices and behaviors in the social sciences (Daniels, Faniel, Fear, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2016;Niu, 2009;Yoon, 2014bYoon, , 2016Yoon, , 2017 as part of a broader drive to understand data practices within the social sciences. While these studies have captured some of the contexts and characteristics of social science data reuse by focusing on specific aspects of data reuse practices, which may overlap with other disciplinary contexts, fewer studies have used theoretical approaches or models to explain social scientists' data reuse behaviors.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have investigated data reuse practices and behaviors in the social sciences (Daniels, Faniel, Fear, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2016;Niu, 2009;Yoon, 2014bYoon, , 2016Yoon, , 2017 as part of a broader drive to understand data practices within the social sciences. While these studies have captured some of the contexts and characteristics of social science data reuse by focusing on specific aspects of data reuse practices, which may overlap with other disciplinary contexts, fewer studies have used theoretical approaches or models to explain social scientists' data reuse behaviors.…”
Section: Problem Statementmentioning
confidence: 99%
“…Reusers assess data for a good fit for the purpose of their study (Faniel, Kansa, Kansa, Barrera-Gomez, & Yakel, 2013), for data quality (Cragin & Shankar, 2006;Van House, 2002), or generally for reusability (Faniel & Jacobsen, 2010). Social scientists are also concerned with choosing good quality, trustworthy data and avoiding data with errors (Yoon, 2014a(Yoon, , 2016(Yoon, , 2017. Assessing data for each of these qualities requires different criteria; some important assessment factors which have been identified include data producers' ability to generate trustworthy data, other reusers' positive experiences using the data, and soundness of methodology used to produce data (Faniel & Jacobsen, 2010;Faniel, Kansa, Kansa, Barrera-Gomez, & Yakel, 2013;Yoon, 2017;Zimmerman, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Because data reusers build their work on other researchers' findings, the process of data reuse involves these interactions and communications with other relevant parties. Most commonly, previous research has found that data reusers contact data producers (the original investigators of the project in which the data for reuse were created) with questions (Niu, 2009;Yoon, 2016aYoon, , 2017. Sometimes mentors have been involved in locating and understanding data (Kriesberg, Frank, Faniel, & Yakel, 2013;Rolland & Lee, 2013).…”
Section: Introductionmentioning
confidence: 99%